The Relationship Between Readiness and Motivation of Early Childhood Education Teachers (RA) in Implementing the Merdeka Curriculum in Tonjong District Brebes Regency - Khoerun Nisa, Try Yatimatul; Ali Formen (Universitas Negeri Semarang, 2025)
Teachers in Early Childhood Education (ECE) institutions in Tonjong District exhibited a high level of readiness (57%) and strong motivation (60.5%) in implementing the Merdeka Curriculum. Teacher readiness and motivation are crucial factors in the successful implementation of the Merdeka Curriculum. This quantitative study, employing a correlational design, aimed to investigate the relationship between ECE teachers' readiness and motivation in implementing the Merdeka Curriculum in Tonjong District, Brebes Regency. A total population of 40 ECE teachers was involved in the study, with all teachers included in the sample. Data was collected through a questionnaire. Spearman's rank correlation test was utilized to analyze the data and test the hypothesis. The results of this study using the Spearman Rank Test obtained a significance value of 0.033, which means that the significance value is less than 0.05, so it can be concluded that there is a significant relationship between the readiness and motivation of RA teachers in implementing the Merdeka Curriculum. From the Spearman Rank Test, a correlation coefficient value of 0.388 was also obtained, which is included in the level of fairly strong relationship strength.